PERBANDINGAN MORFEM –TA DAN –TE ITA PADA VERBA BAHASA JEPANG DALAM ESAI BUKU CHUUKYUU KARA MANABU NIHONGO - Wiryanti, Novi (Humanis; Volume 15. No.1. April 2016)
This paper analyzed the application and meaning of morpheme -ta and -te ita in Japanese verb. The data source was taken from an essay which referred on Chuukyuu Kara Manabu Nihongo. This research was using agih method and the  theories used tenses and aspect by Iori and Shimizu. The theories also carried divide verb in Japanese language by Tsujimura. The analysis result show that morpheme -ta and -te ita on Japanese verb used as tenses and aspect marker. Morpheme -ta on verb functions as past tense marker and shows an action that has been completed. Morpheme -te ita on verb also functions as past tense marker, shows an action that has been completed, and ongoing action.
Keywords: morpheme, tenses, and aspect